2002
DOI: 10.1128/aem.68.6.3121-3125.2002
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Verrucomicrobia -Specific Probe EUB338-III and Fluorescent In Situ Hybridization for Detection of “ Candidatus Xiphinematobacter” Cells in Nematode Hosts

Abstract: Fluorescent in situ hybridization with a 16S rRNA probe specific for Verrucomicrobia was used to (i) confirm the division-level identity of and (ii) study the behavior of the obligate intracellular verrucomicrobium "Candidatus Xiphinematobacter" in its nematode hosts. Endosymbionts in the egg move to the pole where the gut primordium arises; hence, they populate the intestinal epithelia of juvenile worms. During the host's molt to adult female, the endosymbionts concentrate around the developing ovaries to occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 23 publications
(17 reference statements)
3
57
0
Order By: Relevance
“…Many of the OTUs that increase significantly over the chronosequence, such as Bradyrhizobium, Chthoniobacteraceae (genus DA101), Mycobacterium, and Rhodoplanes, indicate increased soil organic matter decomposition and nutrient cycling as conditions become more oligotrophic. Interestingly, we also saw an increase in "Candidatus Xiphinematobacter" in our data, suggest-ing an increase in nematode populations (62) and the potential development of higher trophic levels in the soil ecosystem.…”
Section: Discussionsupporting
confidence: 50%
“…Many of the OTUs that increase significantly over the chronosequence, such as Bradyrhizobium, Chthoniobacteraceae (genus DA101), Mycobacterium, and Rhodoplanes, indicate increased soil organic matter decomposition and nutrient cycling as conditions become more oligotrophic. Interestingly, we also saw an increase in "Candidatus Xiphinematobacter" in our data, suggest-ing an increase in nematode populations (62) and the potential development of higher trophic levels in the soil ecosystem.…”
Section: Discussionsupporting
confidence: 50%
“…Members of the candidate genus Xiphinematobacter populate the intestinal epithelia of juvenile nematode worms (66), ectosymbiotic verrucomicrobia on the marine ciliate Euplotidium act as defensive cells (47), and novel verrucomicrobia have been isolated from the human intestine (16), the gut of the sea cucumber (54), marine sponges (57), and the digestive tract of a marine clamworm (14). Previously, we reported the isolation of several novel verrucomicrobia from the guts of wood-eating termites, including the strain we further investigate here, TAV2, which is a member of the Opitutaceae (64).…”
mentioning
confidence: 99%
“…In these nematode species, Wolbachia seems to be required for successful molting as well as for reproduction of the nematode. In only three genera of plant-parasitic nematodes (Heterodera, Globodera and Xiphinema), bacteria-like endosymbionts-other than Wolbachia-have been found (Noel and Atibalentja 2006;Vandekerckhove et al 2002). On the other hand, we can not exclude the possibility of an insertion of Wolbachia genes into the genome of R. similis, as recently has been shown that these inserts can be transcriptionally active (Hotopp et al 2007).…”
Section: Discussionmentioning
confidence: 79%